Prescription Patterns of Inducers and Inhibitors of Cytochrome P450 and Their Potential Drug Interactions in the Real World: A Cross-Sectional Study - Luis Fernando Valladales-Restrepo; Juan Alberto Ospina-Cano; Brayan Stiven Aristizábal-Carmona; Jorge Enrique Machado-Alba (Adis, Springer Healthcare, 2024)
Abstract Introduction Both the induction and inhibition of cytochrome P450 are associated with multiple pharmacological interactions, which can lead to loss of efficacy or increase the risk of adverse drug reactions. Objective The aim was to determine the prescription patterns of cytochrome P450-inducing and -inhibiting drugs and their contraindicated and major pharmacological interactions in a group of patients from Colombia. Methods This cross-sectional observational study included patients who received drugs that induce or inhibit metabolism and examined their contraindicated and major pharmacological interactions. The patients were identified from a population-based database of drug dispensing. Patients were included between December 1 and December 31, 2021. Inhibitors and inducers of cytochrome P450 were classified based on FDA (Food and Drug Administration) guidelines. Drug interactions were identified using the Micromedex® database. Descriptive, bivariate and multivariable analysis was performed. Results A total of 63,433 patients were analyzed. Antiseizure medications (35.9%) and antifungals (27.6%) were the most used inducers and inhibitors. A total of 30.1% of patients had potential contraindicated or greater interactions. The following factors were associated with a higher probability of presenting a potential pharmacological interaction: being male (OR 1.14; 95% CI 1.10-1.19), aged 18-39 years (OR 1.77; 95% CI 1.67-1.89) or 40-64 years (OR 1.64; 95% CI 1.56-1.72), having neurological diseases (OR 1.28; 95% CI 1.21-1.35), having psychiatric diseases (OR 3.84; 95% CI 3.58-4.13), having rheumatologic diseases (OR 1.32; 95% CI 1.23-1.41), receiving comedications with statins (OR 1.14; 95% CI 1.08-1.19), receiving comedications with analgesics (OR 1.33; 95% CI 1.27-1.38), receiving comedications with antiparasitics (OR 2.88; 95% CI 2.66-3.11) and an increase in the number of medications (OR 1.24; 95% CI 1.23-1.25). Conclusion Among the users of cytochrome P450 inhibitors and inducers, potential contraindications and greater interactions are very common, especially in men under 65 years of age with comorbidities and polypharmacy.